Association of tramadol with risk of myocardial infarction among patients with osteoarthritis. Issue 2 (February 2020) - Wei, J.; Wood, M.J.; Dubreuil, M.; Tomasson, G.; LaRochelle, M.R.; Zeng, C.; Lu, N.; Lin, J.; Choi, H.K.; Lei, G.; Zhang, Y.
Summary: Objective: Tramadol has been widely used among patients with osteoarthritis (OA); however, there is paucity of information on its cardiovascular risk. We aimed to examine the association of tramadol with risk of myocardial infarction (MI) among patients with OA. Design: Among OA patients aged 50–90 years without history of MI, cancer, or opioid use disorder in The Health Improvement Network database in the United Kingdom (2000–2016), three sequential propensity-score matched cohort studies were assembled, i.e., (1) patients who initiated tramadol or naproxen (negative comparator); (2) patients who initiated tramadol or diclofenac (positive comparator); and (3) patients who initiated tramadol or codeine (a commonly used weak opioid). The outcome was incident MI over six-months. Results: Among tramadol and naproxen initiators ( n  = 33, 024 in each cohort), 77 (4.8/1000 person-years) and 46 (2.8/1000 person-years) incident MI occurred, respectively. The rate difference (RD) and hazard ratios (HR) for incident MI with tramadol initiation were 1.9 (95% confidence interval [CI] 0.6 to 2.3)/1000 person-years and 1.68 (95% CI 1.16 to 2.41) relative to naproxen initiation, respectively. Among tramadol and diclofenac initiators ( n  = 18, 662 in each cohort), 58 (6.4/1000 person-years) and 47 (5.1/1000 person-years) incident MIs occurred, respectively. The corresponding RD and HR for incident MI were 1.2 (95%CI -2.1 to 14.1)/1000 person-years and 1.24 (95%CI 0.84 to 1.82), respectively. Among tramadol and codeine initiators ( n  = 42, 722 in each cohort), 127 (6.1/1000 person-years) and 103 (5.0/1000 person-years) incident MI occurred, respectively, and the corresponding RD and HR were 1.1 (95%CI:-0.3 to 2.5)/1000 person-years and 1.23 (95%CI:0.95 to 1.60), respectively. Conclusions: In this population-based cohort of patients with OA, the six-month risk of MI among initiators of tramadol was higher than that of naproxen, but comparable to, if not lower than, those of diclofenac or codeine.